An intermittency factor weighted laminar kinetic energy transition model for heat transfer overshoot prediction. (February 2018) - Qin, Y.P.; Yan, C.; Hao, Z.H.; Wang, J.J.
Highlights: The revised model predicts overshoot successfully. The occurrence of overshoot is analyzed. An algebraic intermittency factor is proposed. The intermittency factor is revised to achieve acceleration. Abstract: An intermittency factor weighted laminar kinetic energy transition model appropriate for the prediction of overshoot in the transition region is proposed. Based on the hypersonic laminar kinetic energy transition model, study finds that the model predicts the overshoot when the transition onset is near the front of the configuration with a short transition zone, and greater gradients of relevant variables account for this circumstance. Therefore, the thought that accelerating the forming process of turbulent boundary layer in the late transition region to make greater variable gradients comes into being. Considering the convective and diffusive timescales of disturbances, an algebraic intermittency factor is presented and involved in the small-scale viscosity. In order to achieve the acceleration, compared with the DNS data as well, the intermittency factor is revised for a further step. Finally, the large-scale and small-scale viscosities are weighted by the revised intermittency factor. The revised model has been applied to flat plate boundary layer and boundary layer transitions over a blunt cone at different Reynolds numbers test cases. The results demonstrate the capacity of the model to reproduce overshoot with a reasonable degree of accuracy and reflect the effect of Reynolds number successfully. The revision originates from the perspective of transition model construction. A more sophisticated physics-based description of transition would be more preferable.